Clinical Outcomes and Biologic Costs of Switching Between Tumor Necrosis Factor Inhibitors in US Veterans with Rheumatoid Arthritis. Issue 8 (August 2016) - Cannon, Grant; DuVall, Scott; Haroldsen, Candace; Caplan, Liron; Curtis, Jeffrey; Michaud, Kaleb; Mikuls, Ted; Reimold, Andreas; Collier, David; Joseph, George; Harrison, David; Sauer, Brian
Abstract Introduction The purpose of this study was to evaluate clinical outcomes and drug/administration costs of treatment with tumor necrosis factor inhibitor (TNFi) agents in US veterans with rheumatoid arthritis (RA) initiating TNFi therapy. The analysis compared patients initiating and continuing a single TNFi with patients who subsequently switched to a different TNFi. Methods Data from patients enrolled in the Veterans Affairs Rheumatoid Arthritis (VARA) registry who initiated treatment with adalimumab, etanercept, or infliximab from 2003 to 2010 were analyzed. Outcomes included duration of therapy, Disease Activity Score based on 28 joints (DAS28), and direct drug and drug administration costs. Results Of 563 eligible patients, 262 initiated a single TNFi therapy, 142 restarted their initial TNFi after a ≥90-day gap in treatment (interrupted therapy), and 159 switched to a different TNFi. Patients who switched had higher mean DAS28 before starting TNFi therapy than patients with single or interrupted therapy: 5.3 vs 4.5 or 4.6, respectively. Mean duration of the first course was 34.3 months for single therapy, 18.3 months for interrupted therapy, and 17.7 months for switched therapy. Mean post-treatment DAS28 was highest for patients who switched TNFi. Mean annualized costs for first course were $13, 800 for single therapy, $13, 200 for interrupted therapy, and $14, 200 for switched therapy; mean annualized costs for second course were $12, 800 for interrupted therapy and $15, 100 for switched therapy. Conclusion Patients who switched TNFi had higher pre-treatment DAS28 and higher overall costs than patients who received the same TNFi as either single or interrupted therapy. Funding This research was funded by Immunex Corp., a fully owned subsidiary of Amgen Inc., and by VA HSR&D Grant SHP 08-172.